PENGARUH METODE MAKE A MATCH TERHADAP PRESTASI BELAJAR SISWA KELAS V MATA PELAJARAN IPAS DI MI DARUL AMIEN KECAMATAN GAMBIRAN KABUPATEN BANYUWANGI - Ihya Ulumuddin; Meliantina Meliantina; Imam Mashuri (PGMI Department of Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2024)
The learning process is closely related to the learning methods used by the teacher. Learning methods are one of the main factors that can encourage students to understand the lesson material presented by the teacher. Appropriate teaching methods play a very important role in helping students understand the material presented. In fact, students will be more interested and enthusiastic about learning if the methods used by the teacher are interesting and easy to understand. One method that is often used in cooperative learning is the Make a Match method. This research aims to determine the influence of the Make a Match method (Variable This research uses a nonequivalent control group design pattern. The population in this study was 24 children. Respondents were taken using purposive sampling technique. The data analysis method uses the T Test with the Paired Sample T test formula with the help of the SPSS 24.00 for Windows computer program. From the results of statistical analysis testing, it is known that the empirical effect of the Make a Match method program (X) on children's learning achievement (Y) is -2.966 (t count). The data was consulted with df. = N- k at the 5% significance level (95% confidence level) the critical value is 1.7958 (t table), so the calculated r calculation result is greater than the critical value r table. Meanwhile the negative sign on the calculated t symbolizes that the class posttest value data experimental value is greater than the control class value. This means that there is a significant influence between the Make a Match method on student learning achievement. So Ha is accepted and Ho is rejected.